Identification of 4‐Anilinoquin(az)oline as a Cell‐Active Protein Kinase Novel 3 (PKN3) Inhibitor Chemotype. (9th May 2022) - Asquith, Christopher R. M.; Temme, Louisa; East, Michael P.; Laitinen, Tuomo; Pickett, Julie; Kwarcinski, Frank E.; Sinha, Parvathi; Wells, Carrow I.; Johnson, Gary L.; Zutshi, Reena; Drewry, David H.
Abstract: Deep annotation of a library of 4‐anilinoquin(az)olines led to the identification of 7‐iodo‐ N ‐(3, 4, 5‐trimethoxyphenyl)quinolin‐4‐amine 16 as a potent inhibitor (IC50 =14 nM) of Protein Kinase Novel 3 (PKN3) with micromolar activity in cells. Compound 16 is a potential tool compound to study the cell biology of PKN3 and its role in pancreatic and prostate cancer and T‐cell acute lymphoblastic leukemia. These 4‐anilinoquin(az)olines may also be useful tools to uncover the therapeutic potential of PKN3 inhibition in a broad range of diseases. Abstract : We developed several small, focused libraries of 4‐anilinoquin(az)olines to explore structure‐activity relationships for the understudied kinase Protein Kinase Novel 3 (PKN3). This led to the identification of compound 16 as a potent PKN3 inhibitor. Compound 16 is a potentially useful tool to study PKN3 biology including links to pancreatic and prostate cancer, along with T‐cell acute lymphoblastic leukemia. These compounds may be useful tools to explore the therapeutic potential of PKN3 inhibition in prevention of a broad range of infectious and systemic diseases.